Porous Interconnected Corrugated Carbon Network (ICCN) Composites
By using porous interconnected corrugated carbon-based network (ICCN) composite materials, combined with the use of metal nanoparticles, the shortcomings in energy density and power density of existing electrochemical capacitors are solved, achieving higher energy storage capabilities and faster charging and discharge rates.
Patent Information
- Application Number
- CN202110481254.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2014-11-18
- Filing Date
- 2015-11-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2035-11-18
AI Technical Summary
Existing electrochemical capacitors have shortcomings in energy density and power density, especially when compared with electrochemical batteries, which cannot meet the needs of many practical applications.
A porous interconnected corrugated carbon-based network (ICCN) composite material was developed to increase energy and power density and enhance cycle stability by placing metal nanoparticles in the pores of the carbon layer, combining the advantages of EDLC and pseudocapacitors.
Improved energy and power density, as well as enhanced cycling stability, provide higher energy storage capabilities and faster charging and discharging rates.
Smart Images

Figure CN113257582B_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese patent application No. 201580072540.3, entitled “Porous Interconnected Corrugated Carbon-Based Network (ICCN) Composite Material”, filed on November 18, 2015.
[0002] Related Applications
[0003] This application claims the benefit of U.S. Provisional Patent Application No. 62 / 081,237, filed November 18, 2014, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0004] The present disclosure relates to porous interconnected corrugated carbon-based network (ICCN) composites with increased energy density and increased power density. Background Art
[0005] Electrochemical capacitors offer significant advantages over conventional storage media (such as batteries and capacitors), providing significantly higher energy density than conventional capacitors, and exhibiting higher power and longer cycle life than batteries. Electrochemical capacitors can be divided into two major categories: electric double layer capacitors (EDLCs) and pseudocapacitors. EDLCs store electrostatic charge at the interface between the electrode and the electrolyte, where the charge accumulates on the electrode surface. The most important attributes of EDLC electrodes are high surface area and high porosity, because the amount of charge accumulation is related to the exposed surface area.
[0006] Recent advances in carbon materials (such as carbon nanotubes, two-dimensional one-atom-thick carbon sheets, and activated carbon (AC)) have enabled their use as active materials in EDLCs. Due to their very high surface area, excellent electrical and thermal conductivity, electrochemical stability, and mechanical properties, two-dimensional one-atom-thick carbon sheets have become one of the most attractive materials for such applications. Although carbon-based EDLCs can provide theoretical capacitances of up to 550 farads / gram, they fall short of requirements for many practical applications, especially when compared to electrochemical batteries. Pseudocapacitors based on redox reactions of electrode materials can have capacitances up to 10 times higher than EDLCs, but their widespread use is limited due to lower power density and poor cycle stability.
[0007] In pseudocapacitors, only surface and near-surface sites can contribute to charge storage via redox reactions, where the electrode materials are commonly used metal oxides or conductive polymers. Among metal oxides, ruthenium oxide (RuO2) is popular due to its very high specific capacitance (1300-2200 farad / g), highly reversible charge-discharge characteristics, wide potential window, and high conductivity (10 5Siemens / cm) and has been widely studied as a material for pseudo-capacitor applications. For the practical application of RuO2 as a pseudo-capacitor electrode, the power density and cycle life must be improved. Summary of the invention
[0008] A porous interconnected corrugated carbon-based network (ICCN) composite material and a method for manufacturing the same are disclosed. The porous ICCN composite material is composed of a plurality of carbon layers that are interconnected and spread apart to form a plurality of pores. Metal nanoparticles are disposed in the plurality of pores.
[0009] The present inventors have focused on developing hybrid systems in which the advantages of EDLCs and pseudocapacitors are combined to overcome the disadvantages of each individual technology. Such hybrid electrochemical capacitors disclosed herein provide improved energy and power density, as well as improved cycling stability. The present inventors have determined that carbon-metal oxide nanocomposites with high electrical conductivity are of interest as electrodes for hybrid electrochemical capacitors, proposing that they will benefit from the electrical conductivity of carbon and the high capacitance of metal oxides, thereby providing a system with both higher energy density and higher power density.
[0010] The present inventors have also identified a method for minimizing the number of steps in the preparation of electrochemical capacitors, including, for example, limiting the necessary number of post-processing steps, and thereby maximizing the potential of these methods for practical scale-up in industry.
[0011] Small supercapacitors, known as micro-supercapacitors, have emerged as a promising energy source for powering microelectronics. The inventors have identified applications for carbon-based / RuO2 electrodes in micro-supercapacitors that extend beyond conventional parallel plate supercapacitors, for example, carbon-based electrodes (such as carbon-based / RuO2 electrodes) are used in micro-interdigitated supercapacitor applications. This significant advance avoids the difficult features of making and processing hybrid materials into patterned microelectrodes.
[0012] Certain desirable features of carbon materials useful for applications described herein include high surface area, controlled porosity, and ease of processing into electrodes. The combination of carbon and metal oxides results in hybrid electrodes with higher specific capacitance than pure carbon electrodes, which has so far limited the energy density of currently commercially available supercapacitors. The subject matter described herein also provides methods for preparing and processing carbon / metal oxide electrodes into supercapacitors with different structures and configurations in a manner that avoids many challenges that exist after traditional preparation and manufacturing processes, particularly for miniaturized electronic products. The inventors have determined and described herein a composite material that can be used to construct an electrode of an energy storage device with increased energy density and increased power density and a commercially scalable method for producing the composite material.
[0013] In one aspect, described herein is a porous interconnected corrugated carbon-based network (ICCN) composite material, comprising: a plurality of carbon layers interconnected to each other and extended to form a plurality of holes; and metal nanoparticles disposed in the plurality of holes. In some embodiments, the porous ICCN has an average minor axis diameter of a plurality of holes, which is in the range of about 2 nanometers to about 550 nanometers. In some embodiments, the porous ICCN has an average minor axis diameter of a plurality of holes, which is in the range of about 10 nanometers to about 450 nanometers, or about 25 nanometers to about 400 nanometers, or about 50 nanometers to about 350 nanometers, or about 75 nanometers to about 300 nanometers, or about 100 nanometers to about 250 nanometers. In some embodiments, the range is about 50 nanometers to about 500 nanometers.
[0014] In some embodiments, a porous ICCN composite material is provided, wherein the metal nanoparticles have a nanoflower shape. In certain applications, the metal nanoparticles are metal particles. In other or yet other embodiments, the metal nanoparticles are metal oxide particles. In some embodiments, the metal nanoparticles are manganese dioxide (MnO2) particles, ruthenium dioxide (RuO2) particles, cobalt oxide (Co3O4) particles, nickel oxide (NiO) particles, iron oxide (Fe2O3) particles, copper oxide (CuO) particles, molybdenum trioxide (MoO3) particles, vanadium pentoxide (V2O5) particles, nickel hydroxide (Ni(OH)2) particles or a combination of one or more thereof.
[0015] In another aspect, a porous ICCN composite material is provided, wherein the electrical conductivity of the plurality of carbon layers is greater than about 0.1 Siemens / meter. In some embodiments, the porous ICCN composite material has an electrical conductivity in the range of about 900 Siemens / meter to about 1750 Siemens / meter. In some embodiments, a porous ICCN composite material is provided having an electrical conductivity greater than about 0.5 Siemens / meter, or greater than about 1 Siemens / meter, or greater than about 5 Siemens / meter, or greater than about 10 Siemens / meter, or greater than about 15 Siemens / meter, or greater than about 25 Siemens / meter, or greater than about 50 Siemens / meter, or greater than about 100 Siemens / meter, or greater than about 200 Siemens / meter, or greater than about 300 Siemens / meter, or greater than about 400 Siemens / meter, or greater than about 500 Siemens / meter. Siemens / meter, or greater than about 600 Siemens / meter, or greater than about 700 Siemens / meter, or greater than about 800 Siemens / meter, or greater than about 900 Siemens / meter, or greater than about 1000 Siemens / meter, or greater than about 1,100 Siemens / meter, or greater than about 1,200 Siemens / meter, or greater than about 1,300 Siemens / meter, or greater than about 1,400 Siemens / meter, or greater than about 1500 Siemens / meter, or greater than about 1600 Siemens / meter, or greater than about 1,700 Siemens / meter.
[0016] Another aspect of the subject matter described herein is a porous ICCN composite material wherein the total surface area per unit mass of the plurality of carbon layers is at least about 1,500 m2 / g, or at least about 2,000 m2 / g, or at least about 3,000 m2 / g, or at least about 4000 m2 / g, or at least about 5,000 m2 / g, or at least about 10,000 m2 / g, or at least about 15,000 m2 / g, or at least about 25,000 m2 / g.
[0017] Yet another aspect of the subject matter described herein is a porous ICCN composite material wherein the surface area coverage of the metal nanoparticles on the plurality of carbon layers ranges from about 10% to about 95%. In some embodiments, the surface area coverage of the metal nanoparticles on the plurality of carbon layers is at least about 15%, or at least about 20%, or at least about 25%, or at least about 30%, or at least about 35%, or at least about 40%, or at least about 45%, or at least about 50%, or at least about 60%, or at least about 70%, or at least about 80%, or at least about 90%, or at least about 95%.
[0018] Another aspect of the subject matter described herein is a porous ICCN composite material, wherein the porous ICCN composite material provides an energy density in the range of about 2 Wh / L to about 41 Wh / L. In certain embodiments, the porous ICCN composite material provides an energy density of at least about 2 Wh / L, or at least about 5 Wh / L, or at least about 10 Wh / L, or at least about 15 Wh / L, or at least about 20 Wh / L, or at least about 25 Wh / L, or at least about 30 Wh / L, or at least about 35 Wh / L, or at least about 40 Wh / L.
[0019] Other aspects of the subject matter are methods for producing porous ICCN composite materials. For example, in one embodiment, the method includes: providing a film comprising a mixture of a metal precursor and a carbon-based oxide; and exposing at least a portion of the film to light to form a porous interconnected corrugated carbon-based network (ICCN) composite material, the porous interconnected corrugated carbon-based network (ICCN) composite material comprising: a plurality of carbon layers interconnected with each other and extended apart to form a plurality of pores; and metal nanoparticles disposed within the plurality of pores, wherein light converts the metal precursor into metal nanoparticles. In yet other or other embodiments, a method for producing a porous ICCN composite material is provided, wherein a film made of a mixture of a metal precursor and a carbon-based oxide is provided, comprising: providing a solution comprising a liquid, a metal precursor, and a carbon-based oxide; placing the solution comprising the liquid, the metal precursor, and the carbon-based oxide on a substrate; and evaporating the liquid from the solution to form a film. In one embodiment, a method for producing a porous interconnected corrugated carbon-based network (ICCN) composite material is provided, comprising: forming a porous ICCN comprising a plurality of carbon layers interconnected with each other and extending apart to form a plurality of pores; and electrodepositing metal nanoparticles within the plurality of pores. In another embodiment, the method comprises providing a membrane made of a mixture of a metal precursor and a carbon-based oxide, comprising: providing a solution comprising a liquid, a metal precursor, and a carbon-based oxide; placing the solution comprising the liquid, the metal precursor, and the carbon-based oxide on a substrate; and evaporating the liquid from the solution to form a membrane. In certain applications, the carbon-based oxide is graphite oxide.
[0020] In another aspect, a method for electrodepositing metal nanoparticles in a plurality of pores comprises: immersing a porous ICCN in an aqueous solution having a metal precursor; and applying an electric current through the porous ICCN to electrodeposit the metal nanoparticles into the plurality of pores. In some embodiments, the electric current has a current density of at least about 250 microamperes per square centimeter. In some embodiments, the electric current has a current density of at least about 350 microamperes per square centimeter, or at least about 450 microamperes per square centimeter, or at least about 550 microamperes per square centimeter, or at least about 650 microamperes per square centimeter, or at least about 750 microamperes per square centimeter, or at least about 1,000 microamperes per square centimeter.
[0021] In one exemplary embodiment, a method for producing a porous ICCN composite material is disclosed. In another exemplary embodiment, a method for producing a porous ICCN composite material is disclosed. In yet another exemplary embodiment, a capacitor is disclosed having a first electrode and a second electrode separated from the first electrode by a dielectric, wherein at least one of the first electrode and the second electrode is formed of a porous ICCN composite material.
[0022] Those skilled in the art will understand the scope of the present disclosure and recognize additional aspects thereof after reading the following detailed description in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings incorporated in and forming a part of this specification illustrate several aspects of the disclosure, and together with the description serve to explain the principles of the disclosure.
[0024] Figure 1 A cross section of a carbon-based oxide sheet is depicted.
[0025] Figure 2 Describes the Figure 1 Cross-section of a porous interconnected corrugated carbon-based network (ICCN) obtained by deoxidation of carbon-based oxide flakes.
[0026] Figure 3 Depicts a cross-section of a porous ICCN composite comprising a porous ICCN composite disposed in Figure 2 Metal nanoparticles inside the pores of the porous ICCN.
[0027] Figure 4 A method for preparing a carbon-based film composite material containing carbon-based oxide flakes and a metal precursor is described.
[0028] Figure 5A Depicts the use of computer-directed lasers to form interdigitated electrodes Figure 4 A portion of the carbon-based film composite material is reduced to Figure 3 Electrode patterns made of porous ICCN composites.
[0029] Figure 5B is used Figure 5A Exploded view of a micro-supercapacitor fabricated using interdigitated electrodes depicted in FIG.
[0030] Figure 5C is depicted fully assembled Figure 5B Isometric view of a micro supercapacitor.
[0031] Figure 5D is depicted in Figure 5A A top view of the interdigitated electrodes is depicted in FIG.
[0032] Figure 6 is a description of the addition of metal nanoparticles to Figure 2 The porous ICCN was prepared Figure 3 Flowchart of the electrodeposition method of porous ICCN composites.
[0033] Fig. 7A is a SEM image of a portion of an electrode comprising a porous ICCN composite.
[0034] Figure 7B yes Fig. 7A Higher magnification of the SEM image.
[0035] Figure 7C is a SEM image of the nanoflower morphology of electrodeposited MnO2.
[0036] Fig.7D is the cross-sectional SEM image of the porous ICCN composite. DETAILED DESCRIPTION
[0037] The embodiments given below enable those skilled in the art to practice the present disclosure. After reading the following description with reference to the accompanying drawings, those skilled in the art will understand the concepts of the present disclosure, and will recognize that the application of these concepts is not particularly discussed herein. It should be understood that these concepts and applications fall within the scope of the present disclosure and the appended claims.
[0038] It should be understood that when an element such as a layer, region, or substrate is referred to as being "above," "on," "in," or extending "above" another element, it may be directly above, directly on, directly in, or directly extending "above" another element, or there may be an intermediary element. In contrast, when an element is referred to as being "directly above," "directly on," "directly in," or directly extending "above," there is no intermediary element. It will also be understood that when an element is referred to as being "connected" or "coupled" to another element, it may be directly connected or coupled to another element, or there may be an intermediary element. In contrast, when an element is referred to as being "directly connected" or "directly coupled" to another element, there is no intermediary element.
[0039] Relative terms such as "below" or "above" or "upper" or "lower" or "horizontal" or "vertical" may be used herein to describe the relationship of one element, layer, or region to another element, layer, or region as described in the figures. It should be understood that these terms and those described above are intended to encompass different orientations of the device in addition to the orientation depicted in the figures.
[0040] For purposes of this disclosure, in certain embodiments, the term extended with respect to a plurality of carbon layers that are extended apart from one another means that a portion of adjacent layers of the carbon layers are separated by at least 2 nanometers. Additionally, for purposes of this disclosure, in certain embodiments, a plurality of carbon layers are also defined as having an electrical conductivity greater than about 0.1 Siemens / meter. Additionally, each of the plurality of carbon layers is defined as having a two-dimensional material that is only a single carbon atom thick.
[0041] Figure 1A cross section of a sheet of a carbon-based oxide 10 having a plurality of one-atom-thick carbon sheets 12 is depicted. An oxygen atom 14 is located between each of the plurality of one-atom-thick carbon sheets 12. Suitable materials for the carbon-based oxide 10 are generally referred to as graphite oxide. Directed light having a power in the range of about 5 milliwatts to about 350 milliwatts causes the oxygen atoms to combine with some of the carbon atoms to form carbon dioxide gas, which forces the plurality of one-atom-thick carbon sheets 12 to separate at the locations. The carbon dioxide gas escapes from the carbon-based oxide 10, thereby deoxygenating the carbon-based oxide 10.
[0042] Figure 2 Describes the Figure 1 A cross section of a porous interconnected corrugated carbon-based network (ICCN) 16 obtained by deoxidizing a carbon-based oxide 10 of a carbon-based oxide of the present invention. The porous ICCN 16 comprises a plurality of extended and interconnected carbon layers 18, which are interconnected and extended to form a plurality of pores 20. The average minor axis diameter of the plurality of pores 20 ranges from 2 nanometers to 550 nanometers. In an exemplary embodiment, the average minor axis diameter ranges from 50 nanometers to 500 nanometers.
[0043] Figure 3 A cross-section of a porous ICCN composite material 22 is depicted, which includes metal nanoparticles 24 disposed within a plurality of pores 20. The metal nanoparticles 24 may be, but are not limited to, manganese dioxide (MnO2) particles, ruthenium dioxide (RuO2) particles, cobalt oxide (Co3O4) particles, nickel oxide (NiO) particles, iron oxide (Fe2O3) particles, copper oxide (CuO) particles, molybdenum trioxide (MoO3) particles, vanadium pentoxide (V2O5) particles, nickel hydroxide (Ni(OH)2) particles, and combinations thereof. In other embodiments, the metal nanoparticles are metal particles including, but not limited to, platinum (Pt), palladium (Pd), silver (Ag), gold (Au), and combinations thereof. Furthermore, in at least some embodiments, the metal nanoparticles have shapes including, but not limited to, nanoflower shapes, flake shapes, and combinations thereof.
[0044] In at least one embodiment, the porous ICCN composite material 22 has an electrical conductivity greater than 900 Siemens / meter. In addition, the total surface area per unit mass of the plurality of extended and interconnected carbon layers 18 ranges from 1500 square meters / gram to 1620 square meters / gram. In addition, the surface area coverage percentage of the metal nanoparticles 24 on the plurality of extended and interconnected carbon layers 18 ranges from about 50% to 95%.
[0045] The porous ICCN composite material 22 provides an energy density in the range of 2 Wh / L to 41 Wh / L when charged in a capacitor configuration. In at least some embodiments, the porous ICCN composite material 22 provides an energy density in the range of 2 Wh / L to 20 Wh / L when charged in a capacitor configuration. In other embodiments, the porous ICCN composite material 22 provides an energy density in the range of 20 Wh / L to 41 Wh / L when charged in a capacitor configuration.
[0046] Figure 4 Described is a method for preparing a carbon-based oxide 10 ( Figure 1 ) and a metal precursor 28. The metal precursor 28 can be, but is not limited to, ruthenium chloride hydrate (RuCl3), cobalt chloride (CoCl2), nickel chloride (NiCl2), vanadium chloride (VCl3), iron chloride (FeCl3), copper chloride (CuCl2), molybdenum chloride (MoCl3), hexachloroplatinate (H2PtCl6), hexachloropalladate (H2PdCl6), tetrachloroaurate (HAuCl4), and combinations thereof.
[0047] The method begins by providing a carbon-based oxide 10, a liquid 30, and a metal precursor 28 in a solution 32 (step 100). The method continues by sonicating the solution 32 to increase the dispersion and suspension of the metal precursor 28 and the carbon-based oxide 10 (step 102). After the sonication, the metal precursor 28 is directly dispersed on the carbon-based oxide 10. The method continues by drop-casting the solution onto a substrate 34 (step 104). Next, a step of evaporating the liquid 30 from the solution 32 is started (step 106). The evaporation of the liquid 30 can be forced drying using heat and airflow or natural drying in a relatively low humidity environment. In at least one embodiment, the liquid 30 is deionized water.
[0048] Figure 5A-5C Describes the manufacturing process with Figure 3 An exemplary method for forming a micro-supercapacitor 36 with a first electrode 38 and a second electrode 40 made of a porous ICCN composite material 22. The electrode pattern 42 designed on a computer 44 can be patterned into a film 26 of a carbon-based composite material on a substrate 34 by using light to reduce a portion of the film 26 of the carbon-based composite material into the first electrode 38 and the second electrode 40. When the computer 44 controls the positioning and power of the light 46 output from the light source 48, the exemplary method starts, so that a portion of the film 26 absorbs the light 46 and is converted into a porous ICCN composite material to realize the first electrode 38 and the second electrode 40 (step 200).
[0049] In this exemplary embodiment, the light source 48 is a laser diode, which is radially positioned by the computer 44 along the radial path R and the arcuate path θ. By using the precision of the laser, a computer-designed pattern (such as the electrode pattern 42) can be made into the film 26 of the carbon-based composite material using a direct-engraved label driver to produce the first electrode 38 and the second electrode 40. The precise control of the light source 48 provided by the computer 44 causes the first electrode 38 and the second electrode 40 to interdigitate. Figure 5B As shown, the first electrode 38 and the second electrode 40 are transferred to the packaging substrate 50 .
[0050] from Figure 5D As can be best seen in the top view of FIG. 1 , the carbon-based oxide 10 acts as a good insulator between the first electrode 38 and the electrode digit 38D and the second electrode 40 and the electrode digit 40D. An exemplary length L of the electrode digits 38D and 40D is about 4800 microns. An exemplary width W of the electrode digits 38D and 40D is about 1770 microns. However, it should be understood that the size of the first electrode 38 and the second electrode 40 is scalable and is only limited on the nanometer scale by the wavelength of the light used to strip the carbon-based oxide 10.
[0051] In particular, Figure 5B An exploded view of a micro-supercapacitor 36 comprising a first electrode 38 and a second electrode 40 is shown, wherein the micro-supercapacitor is composed of a plurality of extended and interconnected conductive carbon layers 18 ( Figure 3 ) of porous ICCN composites 22( Figure 3 ) is made. The porous ICCN composite material 22 has a conductivity in the range of 900 Siemens / meter to about 1738 Siemens / meter. In addition, at least one of the first electrode 38 and the second electrode 40 provides a specific capacitance in the range of 1100 farads / gram to 1400 farads / gram. It should be understood that, optionally, the first electrode 38 or the second electrode 40 can be made of metal, and the remaining one of the first electrode 38 or the second electrode 40 is made of the porous ICCN composite material 22. However, the first electrode 38 and the second electrode 40 are typically laser-scribed from a film 26 transferred to a substrate 50 such as polyethylene terephthalate (PET) or silicon (Si) with an insulating layer 52 such as a silicon dioxide (SiO2) layer.
[0052] The first conductive strip 54 and the second conductive strip 56 are joined to the first electrode 38 and the second electrode 40 to provide conductive terminals to couple to an external circuit (not shown). Exemplary external circuits powered by the micro-supercapacitor 36 can be, but are not limited to, integrated circuits and other electrically powered micro-sized devices. A non-conductive liner 58 covers the portion of the first electrode 38 and the second electrode 40 joined to the first conductive strip 54 and the second conductive strip 56. The liner 58 includes a central window through which the electrolyte 60 is placed in contact with the first electrode 38 and the second electrode 40. A polyimide tape can be used as the liner 58. The electrolyte can be a gel electrolyte, such as pyrolyzed silica (FS) nanopowder mixed with an ionic liquid. An exemplary ionic liquid is 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide. Another suitable gel electrolyte is a hydrogel such as poly(vinyl alcohol) (PVA)-H2SO4. Other electrolytes are also suitable, but the disclosed electrolyte provides a voltage window between a maximum charge voltage and a minimum discharge voltage of about 2.5V.
[0053] Figure 5C A fully assembled micro-supercapacitor 36 is depicted. In this exemplary depiction, the first conductive strip 54 becomes the positive terminal and the second conductive strip 56 becomes the negative terminal. It should be understood that the first conductive strip 54 and the second conductive strip 56 can be made of an electrical conductor such as copper (Cu), aluminum (Al) and / or additional structures composed of the porous ICCN composite material 22.
[0054] Therefore, if Figure 5B and Figure 5C As depicted, the first electrode 38 and the second electrode 40 can be used directly as components of a planar micro-supercapacitor after receiving an electrolyte outer coating. Unlike conventional microfabrication methods, Figure 5A The direct laser scribing technique described in does not require masks, expensive materials, post-processing, or clean room operations. In addition, the direct laser scribing technique is cost-effective and easy to scale.
[0055] Between the macroscale and the nanoscale is the submicron scale, which includes a range of micro-supercapacitors that can be used to power integrated circuits. Thus, these micro-supercapacitors can be integrated with integrated circuits so that the integrated circuits and micro-supercapacitors can be manufactured into a single integrated circuit package.
[0056] The porous ICCN composite material 22 of the present disclosure can also be used to make a relatively large first electrode and a second electrode separated by an electrolyte that provides sufficient charge storage capacity to power an electric vehicle the size of a passenger car. In addition, supercapacitors made according to the present disclosure can also be used to provide power to an industrial power grid during peak power demand. For example, the first electrode 38 and the second electrode 40 of the supercapacitor according to the present disclosure can be made to provide peak power to a megawatt capacity power grid.
[0057] Figure 6 is a method for adding metal nanoparticles to porous ICCN 16 ( Figure 2 ) to prepare Figure 3 Flow chart of an exemplary electrodeposition method of a porous ICCN composite material 22. The electrodeposition process begins by forming a porous ICCN 16 (step 300). The porous ICCN 16 can be formed by forming a carbon-based oxide 10 ( Figure 1 ) is exposed to light from light source 48 ( Figure 5A ) is formed. Although at least one embodiment uses a laser for the light source 48, it should be understood that flash lamps and other equally high intensity light sources can be used to reduce the carbon-based oxide to the porous ICCN 16. The electrodeposition process continues by immersing the porous ICCN 16 in an aqueous solution having a metal precursor 28 (step 302). The porous ICCN 16 is used as a working electrode, and a current is applied through the porous ICCN 16 to achieve the effect of using a plurality of pores 20 ( Figure 2 and Figure 3 ) Electrodeposit the metal nanoparticles 24 (step 304). When the electrodeposition is finished (step 308), the electrodeposition is continued for a predetermined time (step 306).
[0058] In at least one embodiment, the metal particles electrodeposited in the electrodeposition step 304 are manganese dioxide (MnO2) particles. In this case, the metal precursor is 0.02 molar manganese nitrate (Mn(NO3)2) in a 0.1 molar sodium nitrate (NaNO3) solution.
[0059] In an exemplary embodiment, a standard three-electrode electrodeposition setup can be used for the electrodeposition of metal nanoparticles. For example, a porous ICCN 16 is used as a working electrode, silver (Ag) or silver chloride (AgCl) is used as a reference electrode, and platinum foil is used as a counter electrode. The exemplary current applied by the porous ICCN 16 has a current density of about 250 microamperes per square centimeter. The predetermined time for applying the current in the electrodeposition step (304) is proportional to the desired amount of metal nanoparticle deposition. The predetermined time ranges from about 3 minutes to about 960 minutes. In one embodiment, the predetermined time ranges from 30 minutes to 240 minutes. In another embodiment, the predetermined time ranges from 240 minutes to 480 minutes. In another embodiment, the predetermined time ranges from 480 minutes to 960 minutes. Within these predetermined time ranges of the electrodeposition step 304, multiple extended and interconnected carbon layers 18 ( Figure 3 The surface area coverage percentage of the metal nanoparticles on the ) ranges from about 10% to approximately about 95%.
[0060] Synthesis and characterization of 3D macroporous ICCN / MnO2 electrodes
[0061] To experimentally realize energy-dense and high-power supercapacitor electrodes, highly conductive and high-surface-area 3D laser-sliced graphene (LSG) frameworks in the form of interconnected corrugated carbon-based networks (ICCNs) were integrated with MnO2, as Figure 3 Schematically shown. According to our previously reported method, ICCN was fabricated by laser scribing of GO membrane, after which its color changed from golden brown to black. The ICCN was subsequently in situ coated with MnO2 using the electrochemical deposition technique described in the following method section. Note that the ICCN electrode darkened in color after electrodeposition, visually indicating the loading of MnO2. It is well known that the conductivity and mass loading of the active material have a significant impact on the electrochemical behavior of supercapacitor electrodes. Here, the mass loading of MnO2 was controlled by adjusting the deposition current and deposition time. The MnO2 loading was 2 The average deposition rate was estimated to be about 6 μg / min, and the deposition time varied almost linearly.
[0062] In addition to the interesting electrical properties, the ICCN / MnO2 electrodes are monolithic and exhibit excellent mechanical integrity under large mechanical deformations. The ICCN / MnO2 electrodes can be bent significantly without damage. The foldability of the ICCN / MnO2 electrodes was evaluated by measuring their resistance under continuous bending cycles. The resistance change only slightly increased up to a bending radius of 5.0 mm and was fully recovered after straightening, regardless of whether the bending was positive (convex) or negative (concave). It is noteworthy that after 1000 cycles of bending and straightening with a concave bending radius of 5.0 mm, the resistance increased by only about 2.8%.
[0063] The evolution of the morphology corresponding to different deposition times was examined by scanning electron microscopy. Figure 7A-7D . Fig. 7A is a SEM image of a portion of an electrode comprising a porous ICCN composite. Figure 7B yes Fig. 7A Higher magnification of the SEM image. Figure 7C is the SEM image of electrodeposited MnO2 nanoflowers. Fig.7D is the cross-sectional SEM image of the porous ICCN composite.
[0064] SEM micrographs illustrate the general morphology and detailed microstructure of typical samples prepared by 120 minutes of deposition. MnO2 is uniformly coated on the surface of graphene throughout the film. In addition, the electrodeposited MnO2 particle illustrates the nano-flower-shaped hierarchical architecture with MnO2 and a clear interface between the graphene substrate, which is consistent with previous research. A careful inspection of the MnO2 nano-flowers illustrates that they are composed of hundreds of ultra-thin nano-sheets with a thickness of 10-20nm. These nano-sheets are interconnected to form mesoporous MnO2 with a large accessible surface area, thereby providing many electroactive sites that can be used to promote the electrolyte of fast surface faradaic reactions (Faradaic reactions).
[0065] The 3D structure of the ICCN / MnO2 electrode was further analyzed using cross-sectional SEM. Fig.7D The 3D porous structure of ICCN was retained without any agglomerates after MnO2 deposition. The ICCN surface was uniformly coated with MnO2 throughout the cross section. In addition, energy dispersive X-ray spectroscopy (EDS) provided elemental maps of C, O, and Mn, confirming that a uniform MnO2 coating throughout the 3D macroporous framework had been produced.
[0066] XPS was successfully used to better understand the chemical composition and oxidation state of Mn in ICCN / MnO2 electrodes. 3 / 2 and Mn 2p 1 / 2The peaks of Mn 3s doublet are located at 642.1 and 653.9 eV, respectively, with a spin energy separation of 11.6 eV, which is very consistent with the data of Mn 2p state reported previously. Toupin et al. showed that the peak separation of Mn 3s doublet is related to the oxidation state of Mn in manganese oxide, where the reference samples of MnO, Mn3O4, Mn2O3 and MnO2 showed separations of 5.79, 5.50, 5.41 and 4.78 eV, respectively. The in-situ prepared ICCN / MnO2 showed a separation energy of 4.8 eV for the Mn 3s doublet, indicating that the oxide is MnO2, which is further confirmed from the O1s spectrum.
[0067] Assembly and electrochemical performance of symmetric ICCN / MnO2 supercapacitors
[0068] To test the electrochemical performance of the ICCN / MnO2 macroporous framework, a supercapacitor soft pack cell was assembled with two symmetrical electrodes separated by a Celgard M824 ion porous separator and impregnated with a 1.0M Na2SO4 electrolyte. The cell was tested by cyclic voltammetry (CV) over a wide scan rate range of 1mV / s-1000mV / s. For example, considering the ICCN / MnO2 sample with a deposition time of 3 minutes, the supercapacitor showed an almost rectangular CV curve with a scan rate of up to 1000mV / s, indicating excellent charge storage characteristics and ultrafast response time of the electrode. The capacitance of the device manufactured using different deposition times was calculated from the CV curve. Please note that the capacitance is calculated using the total volume of the battery stack rather than a single electrode. This includes the volume of the current collector, active material, separator, and electrolyte.
[0069] The capacitance strength depends strongly on the loading of pseudocapacitive MnO2 and increases significantly with deposition time from 0 to 960 minutes. For example, it is possible to achieve up to about 203 F / cm2 for the sample at a deposition time of 960 minutes. 3 This means that the volumetric capacitance based only on the volume of active material in each electrode is 1136.5 F / cm 3 This value is much higher than activated carbon (60-80F / cm 3 ), carbide-derived carbon (180F / cm 3 ), naked ICCN (12F / cm 3 )、Activated MEGO(60F / cm 3 ) and liquid-mediated chemical conversion graphene (CCG) membranes (263.3F / cm 3 ), indicating that the volumetric specific capacitance of carbon-based electrodes can be significantly improved by incorporating pseudocapacitive materials. In addition, this value is higher than some of the best values previously reported for MnO2-based supercapacitors: 16.1 F / cm for CNT / PPy / MnO2 sponges. 3, graphene / MnO2 / CNT is 130F / cm 3 、CNT / MnO2 is 246F / cm 3 , mesoporous carbon / MnO2 is 108F / cm 3 、Superporous carbon / MnO2 is 90F / cm 3 Additionally, depending on the deposition time, devices with up to about 0.8 F / cm per footprint can be achieved. 2 This is in contrast to the typical capacitance of about 0.3F / cm 2 It compares favorably to commercial carbon supercapacitors.
[0070] This unprecedented performance can be understood by separating the contribution of MnO2 nanoflowers from the average capacitance of the ICCN / MnO2 electrode. s,MnO2 =(Q ICCN / MnO2 -Q ICCN ) / (ΔV×m MnO2 ) minus the charge of bare ICCN to calculate the specific capacitance contributed by MnO2 alone. Here Q is the voltammetric charge, ΔV is the working potential window, and m is the mass. The specific capacitance of MnO2 depends on the mass of the active material reaching a maximum value of 1145F / g, which is about 83% of the theoretical capacitance at a mass loading of 13% of MnO2. This remarkable performance can be attributed to the electrode microstructure, which promotes ion and electron transport and provides a rich surface for charge transfer reactions, thereby ensuring greater utilization of active materials.
[0071] To demonstrate the superior properties of ICCN / MnO2 macroporous electrodes, MnO2 was also electrochemically deposited on both chemically converted graphene (CCG) and gold substrates under the same conditions. CCG / MnO2 not only exhibits lower capacitance, but also its performance drops very quickly at higher charge / discharge rates. This can be attributed to the heavy accumulation of graphene sheets during the manufacture of CCG electrodes, resulting in a significant reduction in surface area and ultimately closing most of the porosity. In addition, Au / MnO2 supercapacitors show extremely low capacitance due to limited surface area and structural properties. On the other hand, ICCN / MnO2 shows about 50F / cm 3The stack capacitance of ICCN / MnO2 is more than four times higher than that of CCG / MnO2 and about three orders of magnitude higher than that of Au / MnO2. The enhanced capacitance and rate performance of ICCN / MnO2 further confirm its optimized structure, which synergistically enhances the effects of effective ion migration and high electroactive surface area, thereby achieving high and reversible capacitive behavior even at high charge / discharge rates. The optimized ion diffusion of the ICCN network is also confirmed by electrochemical impedance spectroscopy, with a response time of 23ms for ICCN compared to 5952ms for CCG electrodes. In fact, ICCN / MnO2 supercapacitors show excellent volumetric capacitance and rate performance compared to commercially available activated carbon supercapacitors, pseudocapacitors, and lithium-ion hybrid capacitors.
[0072] Construction of asymmetric supercapacitors
[0073] Construction of asymmetric supercapacitors. Asymmetric supercapacitors (ASCs) utilize different types of positive and negative electrode materials, which can be charged / discharged in completely separated potential windows in the same electrolyte. They are noteworthy because they provide high capacity at the positive electrode via Faraday reaction, and maintain fast charge / discharge due to the EDL mechanism at the negative electrode. In addition, asymmetric configurations can extend the working voltage window of aqueous electrolytes beyond the thermodynamic limit of water (about 1.2V), resulting in significantly higher specific energy than symmetric supercapacitors using aqueous electrolytes. In fact, asymmetric supercapacitors with aqueous electrolytes based on carbon and NiOOH electrodes are now commercially available from ESMA-ELTON. However, although the construction ensures high capacitance, it has a low cell voltage (<1.5V), which is unfavorable to its energy and power performance. Considering the high pseudocapacitance of ICCN / MnO2 electrodes and the fast charge / discharge of the double-layer capacitance of ICCN electrodes, asymmetric supercapacitors are assembled using ICCN / MnO2 as positive electrodes and ICCN as negative electrodes. Here, the charge balance between the two electrodes is achieved by controlling the deposition time of MnO2 at the positive electrode and the thickness of the graphene film at the negative electrode. The electrochemical performance of the asymmetric cell using ICCN / MnO2 with 13% MnO2 mass loading (3 minutes deposition time) for the positive electrode exhibits ideal capacitive behavior with an approximately rectangular CV curve and a highly triangular CC curve. When the scan rate is increased to an ultra-high speed of up to 10,000mV / s, the CV curve maintains its rectangular shape without obvious distortion, indicating the high rate performance of the asymmetric supercapacitor. Interestingly, the asymmetric cell presents a wide and stable operating potential window of up to 2.0V in an aqueous electrolyte, which should provide high energy density. In addition, as the MnO2 deposition time increases from 3 minutes to 960 minutes, the stack capacitance increases significantly from about 3 to 76F / cm 3, which means that the stored energy and power can be greatly improved in asymmetric structures. These batteries can also maintain their high capacity when faster charging and discharging rates are required. The in situ fabricated supercapacitors are highly flexible and can be folded and twisted without affecting the structural integrity of the device. In addition, the supercapacitors can deliver almost the same capacity even when placed in high bending conditions, serving as a practical energy storage system for flexible electronics.
[0074] Long cycle life is another important feature of commercially viable supercapacitors. In fact, the asymmetric supercapacitor is very stable, as it retains more than 96% of its original capacity after 10,000 charge / discharge cycles tested at a high scan rate of 1000mV / s. The equivalent series resistance (ESR) of the supercapacitor was monitored during the cycling process using a Nyquist plot. The device showed a slight increase in ESR in the first 1000 cycles, with only minor changes in the remaining cycles.
[0075] Three-dimensional interdigitated micro-supercapacitor
[0076] Three-dimensional interdigitated micro-supercapacitors. The development of miniaturized electronic systems such as smart sensors, implantable medical devices and micro-electromechanical systems (MEMS) has led to a growing demand for micro-supercapacitors with high energy density in limited spaces. This property is crucial for the miniaturization of energy storage devices for modern electronic applications. Previous research has focused on increasing the energy density of micro-supercapacitors by using different active materials such as activated carbon, graphene, carbon nanotubes, polymers and metal oxides. The development of micro-supercapacitors with high capacity per footprint area is crucial for the miniaturization of energy storage devices for modern electronic applications. Unfortunately, current state-of-the-art systems still suffer from low area capacity: <11.6 mF / cm for carbon. 2 , conductive polymer is <78mF / cm 2, metal oxides are <56.3 problems. A new hybrid micro-supercapacitor was fabricated in which the positive and negative electrodes are divided into 3D interdigitated structures. The structure was achieved by combining "top-down" LightScribe lithography with "bottom-up" selective electrodeposition. First, 3D interdigitated ICCN microelectrodes were produced by directly writing graphene patterns on GO films using a consumer-grade LightScribe DVD burner. The fabricated device includes 16 in-plane microelectrodes (8 positive and 8 negative electrodes) separated by almost insulating GO, and the distance between the microelectrodes is close enough to keep the ion transport pathway short. Subsequently, MnO2 nanoflowers were selectively electrodeposited on a set of ICCN microelectrodes using a standard 3-cell setup. The width of the microelectrode was adjusted to match the charge between the positive and negative electrodes of the microdevice. The lighter microelectrode corresponds to bare graphene (negative electrode), while the color of the other side becomes darker after MnO2 (positive electrode) electrodeposition. Optical microscopy images showed well-defined patterns and sharp boundaries between microelectrodes.
[0077] Electrochemical characterization shows that the asymmetric micro-supercapacitor provides enhanced volumetric capacitance and rate performance compared to conventional sandwich-type asymmetric supercapacitors. 2 The area capacitance shows similar behavior. This may be due to the planar structure of the microdevice, which leads to better volumetric filling efficiency by eliminating the need for polymer separators that are usually used in sandwich structures to avoid short circuits between electrodes. In addition, the microscale structure of the device leads to a significant reduction in the average ion diffusion pathway between the two microelectrodes. This is consistent with the results of all previous graphene micro-supercapacitors. This is considered to be the highest surface capacitance currently achieved in interdigitated micro-supercapacitors. The stack capacitance is significantly improved to about 250F / cm 3 (The volumetric capacitance of each electrode is 1197F / cm 3 ), which is much higher than the previously reported values for EDLC, pseudo-micro-supercapacitors, and hybrid micro-supercapacitors: 1.3 F / cm for carbon onions 3 , graphene is 2.35-3.05F / cm 3 , CNT is 1.08F / cm 3 , graphene / CNT is 3.1F / cm 3 , carbide derived carbon is 180F / cm 3 (electrode), polyaniline nanofiber: 588F / cm 3 、vanadium disulfide nanosheets are 317F / cm 3 (electrode) and MoS2 nanosheets are 178F / cm 3 .
[0078] discuss
[0079] The energy and power density of ICCN / MnO2-based supercapacitors are superior to current technology. In order to prospect these results with the prior art, many commercially available carbon-based supercapacitors, pseudocapacitors, hybrid supercapacitors and lithium-ion hybrid capacitors have been characterized. These devices are tested under the same dynamic conditions as ICCN / MnO2. For all devices, the volume of the full battery containing current collector, active material, separator and electrolyte is calculated. The energy density of mixed ICCN / MnO2 varies between 22 and 42Wh / l according to the mass load of structure (symmetric, asymmetric and sandwich, interdigitated) and MnO2. In contrast, ICCN / MnO2 hybrid supercapacitors store about 6 times the capacity of the most advanced commercially available EDLC carbon supercapacitors. They are also superior to pseudocapacitors, hybrid supercapacitors and supercapacitor / lithium-ion battery hybrids (lithium-ion capacitors). In addition, ICCN / MnO2 supercapacitors can provide a power density of up to about 10kW / l, which is 100 times faster than high-power lead-acid batteries and 1000 times faster than lithium thin-film batteries.
[0080] To meet the high voltage requirements, supercapacitors are usually put into packs of cells connected together in series. This results in bulky supercapacitor modules that are adequate in some cases but often cause problems in applications where the overall size of the power supply is critical. A different design is proposed here in which an array of individual electrochemical cells is directly manufactured in the same plane and in one step. This construction shows very good control of the voltage and current output. In addition, the array can be integrated with solar cells to achieve efficient solar energy collection and storage.
[0081] In summary, the present disclosure provides a simple and scalable method for making compact, reliable and energy-dense, fast-charging and long-life hybrid ICCN / MnO2 three-dimensional supercapacitors and micro-supercapacitors. Given the widespread use of MnO2 in alkaline batteries (about 10 billion units sold per year (34)) and the scalability of carbon-based materials, ICCN / MnO2 hybrid electrodes in particular offer promise for real-world applications.
[0082] Materials and methods
[0083] Synthesis of ICCN / MnO2, Au / MnO2 and CCG / MnO2 Electrodes
[0084] ICCNs were prepared by focusing a laser beam from a LightScribe DVD burner onto a DVD disc coated with graphite oxide. First, the DVD disc was covered with a gold-coated polyimide (Astral Technology Unlimited, Inc.) film or a polyethylene terephthalate sheet. It was coated with a 2% GO dispersion in water using a doctor blade technique and dried for 5 hours under ambient conditions. A computer-designed image was printed onto graphite oxide to make the appropriate ICCN pattern. MnO2 was then electrodeposited from 0.02M Mn(NO3)2 in 0.1M NaNO3 aqueous solution using a standard three-electrode setup, with a piece of ICCN (1 cm 2 ) as the working electrode, Ag / AgCl as the reference electrode (BASi, Indiana, USA) and platinum foil (2 cm 2 , Sigma-Aldrich) as the counter electrode. By applying 250 μA / cm 2 The deposition was achieved by applying a constant current of 3 to 960 minutes for different time periods. After electrodeposition, the working electrode was washed thoroughly with deionized water to remove excess electrolyte and dried in an oven at 60°C for 1 hour. The amount of MnO2 deposited on the ICCN was determined from the difference in electrode weight before and after electrodeposition using a high-precision microbalance (Mettler Toledo, MX5) with a readability of 1 μg.
[0085] For comparison, MnO2 was electrodeposited on other substrates such as gold-coated polyimide and graphene (CCG) paper. Gold-coated polyimide was obtained from Astral Technology Unlimited, Inc. (Minnesota, USA) and used without further treatment. Graphene paper was produced according to our previously reported method. Gold-coated polyimide and graphene paper were cut into 1 cm 2 to further electrodeposit MnO2 under the same conditions as above.
[0086] Assembly of sandwich hybrid supercapacitors
[0087] The electrodes produced in the previous sections are used to assemble a hybrid supercapacitor with a conventional sandwich structure. Symmetrical and asymmetric supercapacitors are constructed. Symmetrical supercapacitors are assembled by using a 1.0M Na2SO4 aqueous solution as an electrolyte, sandwiching a Celgard M824 (Celgard, North Carolina, USA) separator between two identical electrodes. In an asymmetric structure, ICCN / MnO2 is used as the positive electrode, and ICCN is used as the negative electrode. For ICCN- and CCG-based supercapacitors, a stainless steel (or copper) strip is attached to the electrode using silver paint as a current collector. Before assembly, the electrodes are immersed in an electrolyte for 1 hour to ensure proper wetting.
[0088] Fabrication of interdigitated hybrid micro-supercapacitors
[0089] The manufacturing process of micro supercapacitor is shown in Figure 5B and are described below. First, ICCN interdigitated microelectrodes were printed directly onto a GO film supported on a gold-coated polyimide (or polyethylene terephthalate) substrate using a consumer-grade DVD recorder. Second, MnO2 nanoflowers were grown on a set of interdigitated electrodes using the above electrodeposition setup. The applied current was set at 250 μA / cm 2 The current density was normalized to the active ICCN deposition area, and the mass loading was controlled by adjusting the deposition time. Similarly, symmetric micro-supercapacitors based on ICCN / MnO2 as both positive and negative electrodes were also prepared. Here, the fabrication process was the same except that copper tape was used to connect both sides (rather than one side) of the bare interdigitated ICCN electrode together and used as the working electrode during electrodeposition.
[0090] The hybrid electrodes presented in this disclosure can provide higher energy and power than any patent or disclosed method indicated in the subsequent reference list. They also outperform commercially available carbon-based supercapacitors, pseudocapacitors, hybrid supercapacitors, and lithium-ion capacitors tested under the same conditions.
[0091] This disclosure describes a simple technique for miniaturizing these hybrid supercapacitors to microscale. These micro supercapacitors are capable of achieving over 400 mF / cm 2 The hybrid supercapacitor can also provide an energy density of 22Wh / l, which is more than twice the energy density of lithium thin-film batteries. Clearly, the hybrid supercapacitor is advantageous compared to related technologies.
[0092] Another challenge is the operating voltage of existing supercapacitors, which is typically less than 3V, while capacitors used for general electronics applications are typically in the range of a few volts to 1kV. To address this issue, the present disclosure describes, but is not limited to, an embodiment in which electrochemical cell arrays are directly manufactured on the same plane and in a different design in one step. This construction provides an operating voltage window of 6V. In addition, the present disclosure describes ways to further increase the voltage. These arrays can be integrated with solar cells to create an efficient solar energy collection and storage system.
[0093] The applications of the hybrid supercapacitors described in this disclosure include, but are not limited to, the following areas:
[0094] 1. Portable electronic products: such as mobile phones, computers, and cameras.
[0095] 2. Medical Devices: Life-sustaining and life-enhancing medical devices including pacemakers, defibrillators, hearing aids, pain managers and drug pumps.
[0096] 3. Electric vehicles: Long-life, high-power batteries are needed to improve the electric vehicle industry.
[0097] 4. Space: Long-life, high-power batteries can be used in space to power space systems including rovers, landers, space suits and electronic equipment.
[0098] 5. Military Batteries: The military uses specialized batteries to power a large number of electronic products and equipment. Of course, reduced mass / volume is highly preferred.
[0099] 6. Electric aircraft: An aircraft that runs on electric motors rather than internal combustion engines, with electricity coming from solar cells or batteries.
[0100] 7. Grid scale energy storage: Batteries are widely used to store electrical energy when production (from power plants) exceeds consumption, and when consumption exceeds production, the stored energy is used.
[0101] 8. Renewable Energy: Since the sun doesn’t shine at night and the wind doesn’t blow all the time, batteries have found their way into off-grid power systems to store excess power from renewable energy sources for use in the hours after sunset when the wind isn’t blowing. Of course, high-power batteries can draw energy from solar cells at a higher efficiency than current state-of-the-art batteries.
[0102] 9. Power tools: High-power batteries with long life will enable fast charging of cordless power tools such as drills, screwdrivers, saws, wrenches and grinders. The problem with current batteries is the long charging time.
[0103] 10. Miniaturized electronics: Micro hybrid supercapacitors can be used to provide power to microelectronic devices such as microelectromechanical systems (MEMS), smart sensors, implantable medical devices, and radio frequency identification (RFID) tags, for which high capacity per footprint is critical.
[0104] Supercapacitors now play an important role in the advancement of hybrid and electric vehicles, consumer electronics, military and space applications. There is a growing need to develop hybrid supercapacitor systems to overcome the energy density limitations of the current generation of carbon-based supercapacitors. Here, we demonstrate 3D high-performance hybrid supercapacitors and micro-supercapacitors based on graphene and MnO2 by rationally designing the electrode microstructure and combining the active materials with an electrolyte that operates at high voltage. This results in high-energy hybrid supercapacitors with over 1100 F / cm 3 The hybrid electrode has an ultra-high volumetric capacitance. This corresponds to a specific capacitance of 1145 F / g of the constituent MnO2, which is close to the theoretical value of 1380 F / g. The energy density of the entire device varies between 22 and 42 Wh / l, depending on the device configuration, which is better than the energy density of commercially available double-layer supercapacitors, pseudocapacitors, lithium-ion capacitors, and hybrid supercapacitors tested under the same conditions, and is comparable to the energy density of lead-acid batteries. These hybrid supercapacitors use aqueous electrolytes and are assembled in air without the need for expensive "drying chambers" required to build today's supercapacitors. In addition, we demonstrate a simple technique for making supercapacitor arrays for high-voltage applications. These arrays can be integrated with solar cells for efficient energy harvesting and storage systems.
[0105] Due to the rapidly growing demand for energy in modern life, the development of high-performance energy storage devices has received attention. Supercapacitors are promising energy storage devices with properties that are between those of batteries and conventional capacitors, but they are improving faster than either. Over the past few decades, supercapacitors have become a key component of everyday products by replacing batteries and capacitors in an increasing number of applications. Their high power density and excellent low-temperature performance make them the technology of choice for backup power, cold starting, flash cameras, regenerative braking, and hybrid electric vehicles. Future growth of the technology depends on further improvements in energy density, power density, calendar and cycle life, and production costs.
[0106] According to their charge storage mechanism, supercapacitors are classified as double-layer capacitors (EDLC) or pseudocapacitors. In EDLC, charge is stored by rapid adsorption / desorption of electrolyte ions on high surface area carbon materials, while pseudocapacitors store charge via fast and reversible Faradaic reactions near the surface of metal oxides or conductive polymers. Most of the supercapacitors currently available are symmetrical EDLCs characterized by activated carbon electrodes and organic electrolytes, which provide a cell voltage of up to 2.7V (2). Although commercial EDLCs show high power density and excellent cycle life, they have low energy density due to the limited capacitance of carbon-based electrodes. The specific pseudocapacitance of Faraday electrodes (usually 300 to 1000 F / g) exceeds that of carbon-based EDLCs, but their performance tends to degrade rapidly during cycles (2-4).
[0107] Research over the past few years has demonstrated attractive alternatives to conventional EDLCs and pseudocapacitors by employing hybrid systems. Utilizing both faradaic and non-faradaic methods to store charge, hybrid capacitors can achieve energy and power densities greater than EDLCs without sacrificing the cycling stability and affordability that have limited the success of pseudocapacitors to date. Several combinations of materials such as RuO2(6), Co3O4(7), NiO(8), V2O5(9), Ni(OH)2(10), and MnO2(11) have been investigated for the preparation of hybrid supercapacitors. Among them, MnO2-based systems are particularly attractive because MnO2 is an earth-abundant and environmentally friendly material with a high theoretical specific capacitance of 1380 F / g(12). However, the poor ionic (10 -13 S / cm) conductivity and electron (10 -5 -10 -6S / cm) conductivity usually limits its electrochemical performance. Recent reports show that only ultrathin MnO2 films with a thickness of tens of nanometers can achieve some high-performance results. However, the thickness and area-normalized capacitance of these electrodes are not enough for most applications. A promising approach to achieve practical applications of MnO2 is to incorporate nanostructured MnO2 into high-conductivity carrier materials with high surface areas, such as nickel foam, nickel nanocones, Mn nanotubes, activated carbon, carbon foam, carbon fiber, conductive polymers, carbon nanotubes and graphene. Although promising specific capacitances of 148-410F / g have been achieved, these values can only be obtained at slow charge / discharge rates, and it is found that they drop rapidly with increasing discharge rates. In addition, many of these materials have low packing density and large pore volume, which means that a large amount of electrolyte is required to build the device, which increases the mass of the device without increasing any capacitance. Therefore, the energy density and power density of these systems are very limited at the device level. To address these key issues, we have developed promising hybrid electrodes based on three-dimensional graphene doped with MnO2 nanoflowers. By rationally designing the structure of the graphene substrate to achieve high conductivity, suitable porosity and high specific surface area, it is expected that not only high gravimetric capacitance but also improved volumetric capacitance can be achieved. In addition, the high surface area of the nanostructured MnO2 provides more active sites for Faradaic reactions and shortens the ion diffusion pathways that are critical to achieving its full pseudocapacitance. We show that hybrid supercapacitors based on these materials can achieve energy densities of up to 41Wh / l, compared to 7Wh / l for the most advanced commercially available carbon-based supercapacitors. Interestingly, these graphene / MnO2 hybrid supercapacitors use aqueous electrolytes and are assembled in air without the need to build the expensive "drying chambers" required for today's supercapacitors.
[0108] Despite great efforts in the fabrication of large-scale hybrid supercapacitors, there are only a few studies on the design and integration of hybrid materials into micro-supercapacitors. This is likely due to the complex microfabrication techniques, which usually involve building 3D microelectrodes with micrometer separations. Here, we present a simple but general technique for the fabrication of 3D hybrid micro-supercapacitors based on graphene and MnO2. These microdevices are able to achieve ultrahigh capacitances approaching 400 mF / cm per footprint. 2 , which is the highest value achieved by any micro-supercapacitor. They can also provide energy density of up to 22Wh / l, more than twice that of lithium thin-film batteries. These developments are promising for microelectronic devices such as biomedical sensors and radio frequency identification (RFID) tags, where high capacity per footprint is crucial.
[0109] Rational design of high-performance hybrid supercapacitors. When designing supercapacitor electrodes, special efforts have been made to ensure that they can provide high energy density and high power density. This requires optimizing the preparation conditions to promote ion transport and electron transport within the electrode. However, this is very challenging, especially for metal oxide pseudocapacitors, due to the low conductivity and long ion diffusion pathways of conventional metal oxide films. Therefore, in conventional dense MnO2 thick film electrodes, only the top layer is exposed to the electrolyte, which means that a limited amount of active material participates in charge storage. To address these problems, various approaches have been explored in the literature. For example, the electrochemical utilization of electrodes is improved by using nanostructured MnO2 (such as nanoparticles, nanorods, nanowires and nanoflowers). The porous structure of these electrodes maximizes the area of active materials exposed to the electrolyte and can therefore be discharged compared to the solid electrode surface. Although the system exhibits higher energy density, it still suffers from the inherent low conductivity of MnO2, resulting in low power output. In order to improve the conductivity of MnO2 films, conductive materials (such as carbon powder, carbon nanotubes and graphene) have been introduced into nanostructured MnO2 electrodes. However, the electron carriers must move through smaller inter-particle contact areas that exhibit additional resistance, resulting in poor electron transport from the electrode material to the current collector. An ideal electrode can be obtained by growing MnO2 nanostructures onto ICCNs with high conductivity and high surface area. In this structure, the conductive ICCN acts as a 3D current collector to provide an electronic "highway" for charge storage and delivery, while the nanostructured MnO2 enables fast, reversible Faradaic reactions with short ion diffusion pathways. Another interesting feature of this structure is that each MnO2 nanoparticle is electrically connected to the current collector, so that all nanoparticles contribute to capacity with almost no "dead" material.
[0110] Synthesis and characterization of 3D macroporous ICCN / MnO2 electrodes. To experimentally realize energy-dense and high-power supercapacitor electrodes, ICCNs with high conductivity and high surface area were integrated with MnO2, such as Figure 3 As shown. ICCN is produced by laser scribing a carbon-based film such as graphite oxide (GO), after which the color changes from golden brown to black. The ICCN is then in situ coated with MnO2 using an electrochemical deposition technique as described in the methods section. This in situ growth technique enables MnO2 to be strongly anchored on the ICCN, resulting in reduced contact resistance and better electrochemical utilization of MnO2. After electrodeposition, the color of the ICCN electrode becomes darker, visually indicating the loading of MnO2. It is well known that the conductivity and mass loading of the active material have a significant effect on the electrochemical behavior of the supercapacitor electrode. Here, the mass loading of MnO2 is controlled by adjusting the deposition current and deposition time. The MnO2 loading is 0.25 mA / cm 2The average deposition rate was estimated to be about 6 μg / min, which changed almost linearly with the deposition time.
[0111] In addition to the interesting electrical properties, the ICCN / MnO2 electrodes are monolithic and exhibit excellent mechanical integrity under large mechanical deformations. The ICCN / MnO2 electrodes can be bent significantly without damage. The foldability of the ICCN / MnO2 electrodes was evaluated by measuring their resistance under continuous bending cycles. The resistance change only slightly increased to a bending radius of 5.0 mm, and could be fully recovered after straightening regardless of whether the bending was positive (convex) or negative (concave). It is worth noting that the resistance increased by only about 2.8% after bending and straightening 1000 times with a concave bending radius of 5.0 mm. These measurements indicate that the ICCN / MnO2 electrodes have excellent electromechanical properties, which are highly desirable for applications in flexible and portable electronics.
[0112] The evolution of the morphology corresponding to different deposition times was examined by scanning electron microscopy. The SEM micrographs show the general morphology and detailed microstructure of typical samples prepared by 60 minutes of deposition. MnO2 is uniformly coated on the surface of graphene throughout the film. In addition, the electrodeposited MnO2 particles show a nanoflower-shaped hierarchical architecture with a clear interface between MnO2 and the graphene substrate, which is consistent with previous studies. A careful examination of the MnO2 nanoflowers shows that they are composed of hundreds of ultrathin nanosheets with a thickness of 10-20nm. These nanosheets are interconnected to form mesoporous MnO2 with a large accessible surface area, thereby providing many electroactive sites for electrolytes that can be used to promote fast surface faradaic reactions.
[0113] Use cross-section SEM to further analyze the 3D structure of ICCN / MnO2 electrode. The 3D porous structure of ICCN is retained after MnO2 deposition and is free of any agglomerates. The graphene surface is uniformly coated with MnO2 over the entire cross section. In addition, energy dispersive x-ray spectroscopy (EDS) provides the elemental diagram of C, O and Mn, which confirms that uniform MnO2 coating is produced in the entire ICCN. As a comparative contrast, MnO2 electrodeposition is carried out on both chemically converted graphene (CCG) and gold substrate. Different from ICCN, MnO2 electrodeposition only occurs on the top surface of CCG, and MnO2 thick and dense film is deposited on gold. In addition, compared with ICCN / MnO2, CCG / MnO2 and Au / MnO2 electrodes all show poor mechanical properties.
[0114] XPS was successfully used to better understand the chemical composition and oxidation state of Mn in ICCN / MnO2 electrodes. Mn 2p and Mn 3s spectra. Mn 2p 3 / 2 and Mn 2p 1 / 2The peaks of Mn 3s doublet are located at 642.1 and 653.9 eV, respectively, with a spin energy separation of 11.6 eV, which is very consistent with the data of Mn 2p state reported previously. Toupin et al. showed that the peak separation of Mn 3s doublet is related to the oxidation state of Mn in manganese oxide, where the reference samples of MnO, Mn3O4, Mn2O3 and MnO2 showed separations of 5.79, 5.50, 5.41 and 4.78 eV, respectively. The in-situ prepared ICCN / MnO2 showed a separation energy of 4.8 eV for the Mn 3s doublet, indicating that the oxide is MnO2, which is further confirmed from the O1s spectrum.
[0115] Assembly and electrochemical performance of symmetric ICCN / MnO2 supercapacitors. In order to test the electrochemical performance of the ICCN / MnO2 macroporous framework, a supercapacitor soft pack cell was assembled with two symmetric electrodes separated by a Celgard M824 ion porous separator and impregnated with a 1.0M Na2SO4 electrolyte. The battery was tested by cyclic voltammetry (CV) over a wide scan rate range of 1mV / s-1000mV / s. For example, considering an ICCN / MnO2 sample with a deposition time of 3 minutes, the supercapacitor showed an almost rectangular CV curve with a scan rate of up to 1000mV / s, indicating excellent charge storage characteristics and ultrafast response time of the electrode. The capacitance of the device manufactured using different deposition times was calculated from the CV curve. Please note that the capacitance is calculated using the total volume of the battery stack rather than a single electrode. This includes the volume of the current collector, active material, separator, and electrolyte.
[0116] The capacitance depends strongly on the loading of pseudocapacitive MnO2 and increases significantly with deposition time from 0 to 960 minutes. For example, it is possible to achieve up to about 203 F / cm2 for the sample at a deposition time of 960 minutes. 3 This means that the volumetric capacitance based only on the volume of active material in each electrode is 1136.5 F / cm 3 This value is much higher than activated carbon (60-80F / cm 3 ), carbide-derived carbon (180F / cm 3 ), naked ICCN (12F / cm 3 )、Activated MEGO(60F / cm 3 ) and liquid-mediated CCG membrane (263.3F / cm 3 ), indicating that the volumetric specific capacitance of carbon-based electrodes can be significantly improved by incorporating pseudocapacitive materials. In addition, this value is higher than some of the best values previously reported for MnO2-based supercapacitors: 16.1 F / cm for CNT / PPy / MnO2 sponge 3 , graphene / MnO2 / CNT is 130F / cm 3, CNT / MnO2 is 246F / cm 3 , mesoporous carbon / MnO2 is 108F / cm 3 , and superporous carbon / MnO2 is 90F / cm 3 Additionally, depending on deposition time, up to about 0.8 F / cm per device footprint can be achieved. 2 This is in contrast to the typical capacitance of about 0.3F / cm 2 It compares favorably to commercial carbon supercapacitors.
[0117] Supercapacitors are widely used in a variety of applications that require a large amount of power in a short period of time, where a very large number of charge / discharge cycles or a longer service life is required. However, the operating voltage of existing supercapacitors is very low (<3 volts), while conventional capacitors used for general electronics applications are typically in the range of a few volts to 1 kV. To meet high voltage requirements, supercapacitors are typically put into battery packs connected in series. This results in bulky supercapacitor modules, which are appropriate in some cases, but often cause problems in applications where the overall size of the power supply is critical. Here, we propose a different design in which individual electrochemical cell arrays are directly manufactured in the same plane and in one step. This construction provides flexibility in controlling the output voltage and current of the array. Compared to a single device with an operating voltage of 2V, an array of 3 serial cells extends the output voltage to 6V, while the output capacity (run time) can be increased to 3 times using a parallel array of 3 cells. By using arrays of 3 series in parallel and 3 series in series, both the output voltage and current can be tripled. Although high-voltage supercapacitor arrays have been described using strings of 3 cells, it is possible to increase the number of cells to reach an operating voltage of 100V, which is promising for a variety of applications.
[0118] With the growing interest in "green" systems, solar power generation is gaining popularity in an increasing number of energy-efficient buildings and smart cities. When combined with energy storage systems that store energy during the day, they can be used to make self-powered systems that are promising for street lighting, industrial wireless monitoring, transportation, and consumer electronics applications. Chemical batteries are commonly used in these systems due to their high energy density. Recently, supercapacitors are becoming an alternative because they can capture energy more efficiently due to their short response time. However, these modules are struggling because the energy density of existing supercapacitors is low. Because ICCN / MnO2 hybrid supercapacitors can provide higher energy density, and because they can be manufactured into arrays with high voltage and current ratings, they can be integrated with solar cells for efficient energy harvesting and storage.
[0119] In summary, we have developed a simple and scalable method for fabricating hybrid ICCN / MnO2 three-dimensional electrodes. ICCN with high conductivity and porous structure proved to be an excellent skeleton for MnO2 nanoparticles. The unique structure of these hybrid electrodes allows the effective use of the pseudocapacitive properties of MnO2 while providing convenient transport of both electrolyte ions and electrons. As a result, these supercapacitors exhibit high specific capacitance, ultrafast charge / discharge rates, excellent cycle stability and high power density. They can store up to 6 times more electricity than commercial carbon supercapacitors. These cells are manufactured in air without the need for expensive organic electrolytes or expensive drying chambers required to build today's supercapacitors. Given the widespread use of MnO2 in alkaline batteries (about 10 billion units sold each year) and the scalability of graphene-based materials, we believe that graphene / MnO2 hybrid electrodes offer prospects for real-world applications.
[0120] Synthesis of ICCN / MnO2, Au / MnO2, and CCG / MnO2 electrodes. ICCN was prepared using our previously reported method. Gold-coated polyimide membrane (Astral Technology Unlimited, Inc.) or polyethylene terephthalate membrane was used as the substrate. MnO2 was then electrodeposited from 0.02 M Mn(NO3)2 in 0.1 M NaNO3 aqueous solution using a standard three-electrode setup, where a piece of ICCN (1 cm 2 ) as the working electrode, Ag / AgCl as the reference electrode (BASi, Indiana, USA) and platinum foil (2 cm 2 , Sigma-Aldrich) as the counter electrode. By applying 250 μA / cm 2 The deposition was achieved by applying a constant current of 3 to 960 minutes for different time periods. After electrodeposition, the working electrode was washed thoroughly with deionized water to remove excess electrolyte and dried in an oven at 60°C for 1 hour. The amount of MnO2 deposited on the ICCN was determined from the difference in electrode weight before and after electrodeposition using a high-precision microbalance (Mettler Toledo, MX5) with a readability of 1 μg.
[0121] For comparison, MnO2 was electrodeposited on other substrates such as gold-coated polyimide and graphene (CCG) paper. Gold-coated polyimide was obtained from Astral Technology Unlimited, Inc. (Minnesota, USA) and used without further treatment. Graphene paper was produced according to our previously reported method. Gold-coated polyimide and graphene paper were cut into 1 cm 2 to further electrodeposit MnO2 under the same conditions as above.
[0122] Assembly of sandwich hybrid supercapacitors. Hybrid supercapacitors with conventional sandwich structures were assembled using the electrodes produced in the previous sections. Both symmetric and asymmetric supercapacitors were constructed. Symmetric supercapacitors were assembled by sandwiching a Celgard M824 (Celgard, North Carolina, USA) separator between two identical electrodes using a 1.0M Na2SO4 aqueous solution as an electrolyte. In an asymmetric structure, ICCN / MnO2 was used as the positive electrode, and ICCN was used as the negative electrode. For ICCN- and CCG-based supercapacitors, a stainless steel (or copper) tape was attached to the electrode using silver paint as a current collector. Prior to assembly, the electrodes were soaked in the electrolyte for 1 hour to ensure proper wetting.
[0123] Characterization and Measurement
[0124] The morphology and microstructure of different electrodes were studied by field emission scanning electron microscopy (JEOL 6700) equipped with energy dispersive spectroscopy (EDS) and optical microscopy (Zeiss Axiotech 100). XPS analysis was performed using a Kratos Axis Ultra DLD spectrometer. The thickness of the different components of the device was measured using cross-sectional scanning electron microscopy and a Dektak 6 curve meter. The electrochemical performance of ICCN-MSC supercapacitors was studied by cyclic voltammetry (CV), constant current charge / discharge tests, and electrochemical impedance spectroscopy (EIS). CV tests were performed on a VersaSTAT3 electrochemical workstation (Princeton Applied Research, USA). Charge / discharge and EIS measurements were recorded on a VMP3 workstation (Bio-Logic Inc., Knoxville, TN) equipped with a 10A current booster. The EIS experiment was performed at an amplitude of 10mV at an open circuit potential in the frequency range of 1MHz to 10mHz.
[0125] Porous ICCN composite pore structure
[0126] The pore structure of porous ICCN is analyzed from two forms of carbon-based two-dimensional materials, which are chemically converted graphene (CCG) films and laser-scribed graphene (ICCN) films. CCG sheets are well connected together in a layered structure to form CCG electrodes. The reduced porosity and limited accessibility of electrolyte ions cause the frequency response of CCG electrodes to be slow by about 5 seconds. On the other hand, the ICCN electrode has a well-defined porous structure, so that each graphene sheet in the ICCN network can approach the electrolyte, and thus exhibits a fast frequency response of 23ms. This leads to the enhanced capacitance and rate performance observed with ICCN / MnO2. The optimized structure of the ICCN electrode synergistically strengthens the effects of both effective ion migration and high electroactive surface area, thereby achieving high reversible capacitance behavior of ICCN / MnO2 even at high charge / discharge rates.
[0127] By performing AC impedance measurements in the frequency range of 1MHz to 10MHz, the capacitive behavior of CCG / MnO2 and ICCN / MnO2 mixed electrodes can be further understood. For each of these batteries, MnO2 was electrodeposited for 120 minutes. The Nyquist plot consists of a sharp peak in the low-frequency region and a semicircle in the high-frequency region. Compared with CCG / MnO2, ICCN / MnO2 supercapacitors show much smaller semicircle diameters, which indicates more efficient charge transfer on the electrode surface. In addition, in the low-frequency region, more vertical straight lines are observed for porous ICCN / MnO2 electrodes, indicating that these electrodes have faster ion diffusion and almost ideal capacitive behavior. The intercept of the Nyquist curve on the real axis is about 1.5Ω, indicating the high conductivity and low electrode internal resistance of the electrolyte. These results show that the microstructure of the graphene electrode has a strong influence on the electrochemical properties of its composite with metal oxides.
[0128] Directly fabricate hybrid micro-supercapacitor arrays for high voltage applications. It is highly desirable to develop supercapacitor arrays with larger operating voltages to meet the energy and power requirements of the systems on which they are integrated. This is very important, considering that the operating voltages of existing supercapacitors are relatively low (<3 volts), while capacitors used for general electronics applications are typically in the range of a few volts to 1 kV. To meet the high voltage requirements, supercapacitors are typically put into packs of cells connected together in series. Here, we propose a different design in which arrays of individual electrochemical cells are directly fabricated on the same plane.
[0129] First, the circuit is designed using appropriate computer software and patterned directly on the graphite oxide film coated on the DVD disc. It is also possible to design the pattern to make a series / parallel combination of supercapacitor banks to meet the voltage (series) and current (parallel) requirements of the system on which the supercapacitor bank is integrated.
[0130] The second step is to deposit the MnO2 nanoflowers. Here, the deposition process differs depending on whether it is a symmetric array or an asymmetric array. Ideally, a gel electrolyte is used to prevent leakage into other cells in the array.
[0131] Calculation. The capacitance of the supercapacitor was calculated based on both the cyclic voltammetry (CV) curve and the constant current charge / discharge curve (CC). For the CV technique, the capacitance was calculated by integrating the discharge current (i) versus potential (E) plot using the following equation:
[0132]
[0133] where ν is the scan rate (V / s), and ΔE is the operating potential window.
[0134] The capacitance was also calculated from the charge / discharge (CC) curves at different current densities using the following formula:
[0135]
[0136] where i app is the applied current (in amperes, A), and dV / dt is the slope of the discharge curve (in volts / second, V / s). The specific capacitance is calculated based on the area and volume of the device stack according to the following equation:
[0137]
[0138]
[0139] Where A and V refer to the area of the device (cm 2 ) and volume (cm 3 ). Taking the volume of the device stack into account, calculate the stack capacitance (F / cm 3 ). This includes the active material, current collector, and separator with electrolyte.
[0140] The energy density of each device is obtained from the formula given by equation (5):
[0141]
[0142] Where E is the energy density in Wh / l, C v is obtained from the constant current charge / discharge curve using equation (3) in F / cm 3 ΔE is the volumetric stack capacitance in volts.
[0143] Calculate the power density of each device using the following equation:
[0144]
[0145] where P is the power density in W / l and t is the discharge time in hours.
[0146] Since most volumetric specific capacitances reported in the literature are based only on the volume of the active material, for comparison purposes we applied the same calculation using the following equation:
[0147] The volumetric specific capacitance of the device,
[0148]
[0149] where V is the volume of active material on both electrodes
[0150] Volumetric capacitance per electrode,
[0151] c v(电极) =4×C v(装置) (9) (8)
[0152] Asymmetric cells. To achieve optimal performance with an asymmetric supercapacitor, there should be a charge balance between the positive and negative electrodes. The charge stored by each electrode depends on its volumetric specific capacitance (C v(电极) ), electrode volume (V), and the potential window (ΔE) in which the material operates.
[0153] q=C v(电极) ×V×ΔE (9)
[0154] In order to achieve charge balance, the following conditions must be met
[0155] q + =q - (10)
[0156]
[0157] Charge balance is achieved by adjusting the thickness of the positive and negative electrodes.
[0158] Comparison with commercial energy storage systems. In order to properly understand the ICCN / MnO2 hybrid supercapacitors and micro-supercapacitors, the performance of a wide range of commercially available energy storage systems was compared. This included activated carbon supercapacitors, pseudocapacitors (2.6V, 35mF), battery-supercapacitor hybrids (lithium-ion capacitors) (2.3V, 220F), aluminum electrolytic capacitors (3V, 300μF) and lithium thin-film batteries (4V / 500μAh). Activated carbon supercapacitors of different sizes were tested: small (2.7V, 0.05F), medium (2.7V, 10F) and large (2.7V, 350F). Due to the limitation of the measurement equipment that provides a maximum current of 10A, the power consumption at 160mA / cm 3The activated carbon macrocells (2.7 V, 350 F) were tested at a lower current density of 2.5 V. All devices were characterized under the same dynamic conditions as the ICCN / MnO2 hybrid supercapacitors and micro-supercapacitors.
[0159] Those skilled in the art will recognize improvements and modifications to the embodiments of the present disclosure. All such improvements and modifications are considered within the scope of the concepts disclosed herein and the appended claims.
Claims
1. A method for producing a porous interconnected corrugated carbon-based network (ICCN) composite material, comprising: providing a film comprising a mixture of a metal precursor and a carbon-based oxide; as well as exposing at least a portion of the film to form a porous interconnected corrugated carbon-based network (ICCN) composite material, the porous interconnected corrugated carbon-based network (ICCN) composite material comprising: a plurality of one-atom thick carbon layers interconnected and directly connected to each other and extending apart to form a plurality of pores; as well as Metal nanoparticles are disposed within the plurality of holes, wherein light converts the metal precursor into the metal nanoparticles.
2. The method of claim 1 , wherein providing the film made of a mixture of the metal precursor and the carbon-based oxide comprises: providing a solution comprising a liquid, the metal precursor, and the carbon-based oxide; placing the solution having the liquid, the metal precursor, and the carbon-based oxide on a substrate; and evaporating the liquid from the solution to form the film.
3. The method of claim 1 or 2, wherein the metal nanoparticles have a surface area coverage of at least 5% on the plurality of single-atom thick carbon layers.
4. The method of any one of claims 1-3, wherein the surface area coverage of the metal nanoparticles on the plurality of single-atom thick carbon layers ranges from 10% to 95%.
5. The method of any one of claims 1-4, wherein the metal nanoparticles have a percent surface area coverage of at least 15% on the plurality of single-atom thick carbon layers.
6. The method of any one of claims 1-5, wherein the metal nanoparticles have a surface area coverage of at least 30% on the plurality of single-atom thick carbon layers.
7. The method of any one of claims 1-6, wherein the metal nanoparticles have a surface area coverage of at least 80% on the plurality of single-atom thick carbon layers.
8. The method according to any one of claims 1-7, wherein the porous interconnected corrugated carbon-based network (ICCN) composite material comprises a minor axis diameter ranging from 50 nm to 500 nm.
9. The method of any one of claims 1-8, wherein at least one of the metal nanoparticles comprises a nanorod, a nanowire, or a nanoflower.
10. The method according to any one of claims 1 to 9, wherein the metal nanoparticles have a nanoflower shape.
11. The method according to any one of claims 1 to 10, wherein the metal nanoparticles are metal particles or metal oxide particles.
12. The method according to claim 11, wherein the metal nanoparticles are manganese dioxide (MnO2) particles, ruthenium dioxide (RuO2) particles, cobalt oxide (Co3O4) particles, nickel oxide (NiO) particles, iron oxide (Fe2O3) particles, copper oxide (CuO) particles, molybdenum trioxide (MoO3) particles, vanadium pentoxide (V2O5) particles, nickel hydroxide (Ni(OH)2) particles, or a combination thereof.
13. The method according to any one of claims 1-12, wherein the electrical conductivity of the porous interconnected corrugated carbon-based network (ICCN) composite material is greater than 0.1 Siemens / meter.
14. The method according to any one of claims 1 to 13, wherein the electrical conductivity of the porous interconnected corrugated carbon-based network (ICCN) composite material ranges from 900 Siemens / m to 1750 Siemens / m.
15. The method of any one of claims 1-14, wherein the porous interconnected corrugated carbon-based network (ICCN) composite material has a total surface area of the plurality of single-atom thick carbon layers per unit mass of at least 1,500 square meters per gram.
16. The method of any one of claims 1-15, wherein each of the plurality of one-atom thick carbon layers is a two-dimensional material having only a single carbon atom thickness.
17. The method according to any one of claims 1-16, wherein individual graphene sheets in the porous interconnected corrugated carbon-based network (ICCN) composite material are accessible to an electrolyte.
Citation Information
Patent Citations
Modified grapheme preparation method
CN103787328A
Capacitor with electrodes made of an interconnected corrugated carbon-based network
WO2013134207A1
Material and applications therefor
CN103097288A